Life Expectancy of Evaporating Capillary Bridges Predicted by Tertiary Creep Modeling - Guével, Alexandre; Mielniczuk, Boleslaw; Veveakis, Manolis; Hueckel, Tomasz (Frontiers in Mechanical Engineering, 2022)
The evaporation of capillary bridges is experimentally investigated at the microscale through a three-grain capillary cluster. This setting provides the minimum viable description of Haines jumps during evaporation, that is, capillary instabilities stemming from air entry into a saturated granular material. The displacement profile of a meniscus is obtained via digital image correlation for different grain materials, geometries, and separations. While it is well known that Haines jumps are triggered at the pore throat, we find that these instabilities are of three types depending on the separation. We also provide a temporal characterization of Haines jumps; we find that they are accurately described, as tertiary creep instabilities, by Voight's relation, similarly to landslides and volcanic eruptions. This finding extends the description of capillary instabilities beyond their onset predicted by Laplace equilibrium. Our contribution also paves the way for a microscopically-informed description of desiccation cracks, of which Haines jumps are the precursors.